Effect of The Water Salinity Level on Yield and Fruit Quality of Pepper (Capsicum annuum L.) - KARA, TEKIN; EKMEKCI, EMINE; APAN, MEHMET (Asian Journal of Chemistry, 2010)
The effect of five irrigation water salinities (0.34, 1.00, 2.50, 4.00, 6.00 dS m-1) and two Ca:Mg ratio levels (1:1 and 3:1) on yield and some quality parameters of a pepper (Capsicum annuum L.) were investigated under greenhouse conditions. A full randomized factorial experiment was conducted on April 18, 2005 at the Greenhouse Station, Ondokuz Mayis University. Yield, fruit quality data were collected. The saline irrigation water was obtained by adding NaCl, CaCl2 and MgSO4 to tap (control) water. According to treatment results the yield decreased with increasing salinity level with starting at salinity level of 1.00 dS m-1 and continued to 6.00 dS m-1, p < 0.05. But there is no significant Ca : Mg ratios effect to yield. The loss in yield reaches 80 % with increasing salinity level. Increasing salinity level resulted in smaller fruit size, plant height and root depth. However, increasing salinity level resulted in increase oven-dry mineral material of the fruits, leaves and the stem.